Is it possible to select team roles to form a successful team: Is team effectiveness bound by the resources available? - Wood, Katherine (2010)
Teamwork within organisations is an area which generates a vast amount research. With the use of teamwork growing in firms and the need for many companies to try to refine both the operation of teams and the quality of their output, it is interesting to examine the variables that can affect being able to produce the ‘ideal team’. Alongside these variables comes the issue of organizations having the necessary resources available to create the preferred team.